Revision of the amphiamerican genus Mysidium Dana, 1852 (Crustacea: Mysida: Mysidae), with descriptions of two new species and the establishment of two new subgenera - Wittmann, Karl J.; Wirtz, Peter (European Journal of Taxonomy, 2019)
Revised definitions are given for the genus Mysidium Dana, 1852, and its eight previously known species, based on material from Curaçao, Bonaire and SE-Brazil, along with the evaluation of published data. Type material of Diamysis columbiae Zimmer, 1915, M. cubanense Băcescu & Ortiz, 1984 and M. rubroculatum Băcescu & Ortiz, 1984 is examined. A lectotype is designated for D. columbiae Zimmer, 1915, a senior synonym of Mysidium columbiae (Zimmer, 1915). Two new species are described, M. triangulare Wittmann sp. nov. from Curaçao and M. antillarum Wittmann sp. nov. from Curaçao and Bonaire. Known ranges are extended by first records of M. cubanense from Curaçao and Bonaire and of M. integrum W.M. Tattersall, 1951 from SE Brazil. Three morphologically different groups are established at the subgeneric level: (1) the nominotypical subgenus Mysidium Dana, 1852 with M. gracile (Dana, 1852), M. integrum, M. cubanense, M. rubroculatum and M. triangulare sp. nov. from the West Atlantic plus M. rickettsi Harrison & Bowman, 1987 from the East Pacific; (2) Occimysidium Wittmann subgen. nov. represented only by M. pumae Ortiz, Hendrickx & Winfield, 2017 from the Pacific coast of Mexico; and finally (3) Orientomysidium Wittmann subgen. nov. comprising M. columbiae and M. antillarum sp. nov. from the West Atlantic. The poorly known M. iliffei Băcescu, 1991 is not assigned to any subgenus. A key to the resulting three subgenera and ten nominal species of the genus Mysidium is given.